2012
DOI: 10.1002/hbm.22129
|View full text |Cite
|
Sign up to set email alerts
|

Changes in resting‐state functionally connected parietofrontal networks after videogame practice

Abstract: Neuroimaging studies provide evidence for organized intrinsic activity under task-free conditions. This activity serves functionally relevant brain systems supporting cognition. Here, we analyze changes in resting-state functional connectivity after videogame practice applying a test-retest design. Twenty young females were selected from a group of 100 participants tested on four standardized cognitive ability tests. The practice and control groups were carefully matched on their ability scores. The practice g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 93 publications
1
31
0
Order By: Relevance
“…In the trained group, increased frontoparietal, parietostriatal and frontostriatal iFC was observed, with increases in frontoparietal and parietostriatal iFC being associated with improvements in LSAT performance (though it should be noted that the brain-behavior correlations were uncorrected for multiple comparisons). Another study (Martinez et al, 2013) also observed increased iFC within frontoparietal and lateral and medial temporal networks (also at uncorrected thresholds) following 4 weeks of practice on a puzzle-solving game. As in the study by Jolles et al (2013), it is possible that the increased iFC within higher-level cognitive networks observed in these two studies reflects the fact that even after practice performance was not asymptotic, and required the continued scaffolding support of widespread increases in iFC.…”
Section: Effects Of Practice and Training On Ifcmentioning
confidence: 85%
“…In the trained group, increased frontoparietal, parietostriatal and frontostriatal iFC was observed, with increases in frontoparietal and parietostriatal iFC being associated with improvements in LSAT performance (though it should be noted that the brain-behavior correlations were uncorrected for multiple comparisons). Another study (Martinez et al, 2013) also observed increased iFC within frontoparietal and lateral and medial temporal networks (also at uncorrected thresholds) following 4 weeks of practice on a puzzle-solving game. As in the study by Jolles et al (2013), it is possible that the increased iFC within higher-level cognitive networks observed in these two studies reflects the fact that even after practice performance was not asymptotic, and required the continued scaffolding support of widespread increases in iFC.…”
Section: Effects Of Practice and Training On Ifcmentioning
confidence: 85%
“…We obtained a statistical map (p values) per band (5) and condition (3), which were used as gold standard for finding potential disruptions in patients 1 and 2. We considered statistically significant the uncorrected p<0.005 (cluster size 10), since any statistical contrast passed TFCE-based permutations to correct for multiple comparisons, probably due to the high intra-subject variability of this EEG-informed fMRI relationships Mantini et al 2007) and the small sample size (Martinez et al 2013).…”
Section: Eeg-fmri Analyses: Eeg-informed Fmrimentioning
confidence: 99%
“…T h e i n p u t m a t r i x h a d n voxels *(n conditions *n subjects *n Volumes ) dimensions equals to n voxels * (2 conditions *7 subjects *120 Volumes ) dimensions in our case. The outputs from this TC-GICA were 25 Independent Component (IC) spatial maps, which were used to identify large-scale resting state networks (Damoiseaux et al 2006;Martinez et al 2013;Smith et al 2009). …”
Section: Rsfmri Standalone: Ica Analysesmentioning
confidence: 99%
See 2 more Smart Citations